Application of "parachute" technique for free flap reconstruction in advanced tongue cancer after ablation without lip-jaw splitting: A retrospective case study. Issue 33 (August 2019) - Liu, Chin-Jui; Fang, Ku-Hao; Chang, Chang-Cheng; Lin, Erh-Ti; Chang, Geng-He; Shen, Jen-Hsiang; Chen, Yu-Tsung; Tsai, Yao-Te
Abstract : Abstract: The hemi or subtotal/total glossectomy is usually approached by lip-jaw splitting procedure for advanced tongue cancer ablation. This highly invasive procedure can cause facial disfiguration, bone malunion, and osteoradionecrosis. The aim of this study is to compare the surgical outcome in free flap tongue reconstruction between novel parachute technique in an intact jaw and the conventional lip-jaw splitting procedure after tongue cancer ablation. In this study, parachute technique was adopted for free flap inset in patients without mandibulotomy. We retrospectively reviewed patients who have received primary advanced tongue cancer resection and free flap reconstruction during April, 2008 to January, 2015. Patients were divided into 2 groups. Group A was undergoing parachute technique without lip-jaw splitting. We sutured all the strings through the edges of defect in the first step and through the matching points of flap margin in the second step from outside the oral cavity. Then, the strings were pulled and the flap was parachuted down on the defects after all the matching points were tied together. In group B, the patients received conventional lip-jaw splitting procedure. Student t test was used for results analysis. There were 15 patients (n = 15) in group A and 15 patients (n = 15) in group B. In the patients receiving parachute technique, operation time showed 34 minutes ( P = .49) shorter, hospital stay showed 4 days ( P = .32) shorter, and the infection rate of surgical site showed 6.6% ( P = .64) less than with conventional technique. The survival rates of the flaps were both 100% without revision. The parachute technique is an effective and more accessible method for free flap setting in cases of tongue reconstruction without lip-jaw splitting, and provides patients with better aesthetic appearance.